Determination of Catechins and Antioxidant Properties of Commercial Green and Black Teas - Srividhya, B.; Raj , V.; Subramanian, R. (Asian Journal of Chemistry, 2011)
Catechins and antioxidant activity of commercial green tea and black tea were determined and compared with each other. Catechins were measured by HPLC method. Antioxidant activity was assessed by measuring the ability to scavenge DPPH radical, reduction Fe(III) to Fe(II) and scavenging effect of hydrogen peroxide. The epigallocatechin gallate, epigallocatechin, epicatechin gallate, epicatechin and (+) catechin in green tea was found to be higher than black tea. The DPPH activity and reducing power of green tea were found to be higher when compared to black tea. But the scavenging effect of hydrogen peroxide on black tea showed higher than green tea. The results clearly indicated that green tea had higher amount of individual catechins and antioxidant activity than black tea sample.